I modi della Twitter fiction (ENTHYMEMA, 2023)
Since its very foundation, the microblogging social Twitter has been the venue of some important narrative experimentations with the short-story form. Moving from the mapping of such practices of Twitterature, classified mainly as playful rewriting experiences or collective creations, this article then focuses on three works of Twitter fiction—Jennifer Egan’s Black Box (2012), Eliott Holt’s Evidence: Story of a Crime (2012) and Teju Cole’s Hafiz (2014)—in order to show how these examples may be regarded as dealing more with a medium specificity that goes beyond the simple constraint of brevity. As such, similar examples deploy a reflexive attitude towards the digital medium and its conditions and epitomize a manner of critical engagement with the very possibilities and modalities of the Twitter fiction itself.
Keywords: Twitter; Twitter Fiction; Narrative; Digital Literature; Short Story